A preliminary study of cortical morphology in schizophrenia patients with a history of violence. (30th June 2019) - Storvestre, Guttorm Breivik; Valnes, Lars Magnus; Jensen, Arvid; Nerland, Stener; Tesli, Natalia; Hymer, Knut-Erik; Rosaeg, Cato; Server, Andres; Ringen, Petter Andreas; Jacobsen, Morten; Andreassen, Ole Andreas; Agartz, Ingrid; et al.
Highlights: Violence in schizophrenia is related to increased cortical folding. Violence in schizophrenia is related to reduced cortical thickness. Limited sample size calls for replication of results. Abstract: Clinical studies of patients with schizophrenia and a history of violence are challenging both from an ethical and practical perspective, and the neurobiological underpinnings remain largely unknown. We here present a comprehensive account of the brain cortical characteristics associated with violence in schizophrenia. We obtained 3T MRI scans and thorough clinical characterization of schizophrenia patients with a history of violence (murder, attempted murder, criminal assault, SCZ-V, n = 11), schizophrenia patients with no history of violence (SCZ-NV, n = 17), and healthy controls (HC, n = 19). Cortical thickness, area, and folding were analyzed vertex-wise across the cortical mantle (FreeSurfer). SCZ-V had significantly increased cortical folding in the visual and orbitofrontal cortex, and reduced cortical thickness within the precentral-, parietal-, temporal-, and fusiform cortex compared to SCZ-NV, as well as widespread regional thinning and increased folding compared to HC. There were no group differences in cortical area. A major limitation is the small subject sample. If replicated, the results from this pilot study suggest cortical abnormalities in areas involved in sensory processing, emotion recognition, and reward to be of importance to the neurobiology of violence in schizophrenia.